Experimental and Ab Initio Computational Studies on 4-(Benzhydryloxy)phthalonitrile - Saracoglu, Hanife; Guntepe, Feyizan; Yuksektepe, Cigdem; Caliskan, Nezihe; Saydam, Sinan (Taylor & Francis Ltd, 2011)
Molecular structure, atomic charges, dipole moments, total energies, and vibrational frequencies of 4-(benzhydryloxy)phthalonitrile in the ground state have been calculated using density functional theory (DFT) calculations and compared with the experimental data. Calculated frequencies are in good agreement with the corresponding experimental data. To determine conformational flexibility, the molecular energy profile of the title compound was obtained by semi-empirical (RAM1) calculations with respect to the selected torsion angle, which was varied from -180 degrees to +180 degrees in steps of 10 degrees. In addition, frontier molecular orbitals (FMOs) analysis and thermodynamic properties of the title compound were investigated using theoretical calculations.
Keywords: ab initio calculation; conformational analysis; frontier molecular orbitals; IR spectra; x-ray structure determination